AN EXPLORATORY ANALYSIS OF OPTIMIZING PRODUCT MIX THROUGH HEURISTIC: AN ECLECTIC DECISION - RAY, AMITAVA; SARKAR, BIJAN; SANYAL, SUBIR KUMAR (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
This aim of this paper is to develop an integrated decision model which incorporates product priority and resource center priority in analyzing multi constraint resource environment. The decision model integrates analytical hierarchy process (AHP) and ‘the technique for order preference by similarity to ideal solution’ (TOPSIS) into a single evaluation model in a multi product, multi constraint resource environment. In this paper the inefficiency of traditional TOC algorithm in handling bottleneck is discussed. The decision model compares three alternatives: Standard Theory-Of-Constraints (TOC), Integer linear programming (ILP) analysis and our own solution. The numerical results show that the proposed approach is superior to TOC and ILP analysis and more realistically optimizes resource allocation and measures the performance of the model.